The role of parents in the motivation of young athletes: a systematic review - Gao, Zhendong; Chee, Chen Soon; Norjali Wazir, Mohd Rozilee Wazir; Wang, Jiaxu; Zheng, Xiaojian; Wang, Tao (Frontiers Media, 2024)
Objectives: Parents are one of the main social agents that shape young athletes’ experiences and participation in sports, but they are also the least explored group in the literature. Therefore, the purpose of this study was to conduct a systematic review of research on the role of parents in the motivation of young athletes. Method: The systematic literature review consisted of four electronic databases from which 29 articles published in English and in full-text form in peer-reviewed journals between 1999 and 2023 were retrieved. Results: A total of 29 studies met the eligibility criteria. These studies collectively surveyed 9,185 young athlete participants and 2,191 parent participants. The sample comprised 26 quantitative studies and 3 qualitative studies. The findings underscore that parents play both unique and synergistic multidimensional roles in motivating young athletes. Parents’ positive goals and values, autonomy- supportive parenting styles, moderate parental involvement, positive parent– child relationships, and a parent-initiated task climate are identified as optimal parenting strategies. Conclusion: While parents undeniably play a crucial role in motivating young athletes, the manner and extent of their involvement are key.